Behavioral Finance in Theory and Practice - (:unkn) unknown (IGI GLOBAL, 2014)
Behavioral finance is a new approach in finance literature. The main idea is that investors are not as rational as they are assumed to be. Therefore, financial markets could be better understood by using models that capture the effects of both rational and irrational investors. The critics of behavioral finance could be grouped into two main categories: limits of arbitrage and psychological factors. This chapter concentrates on both challenges and possible contributions of behavioral finance theory to the modern finance theory, which is mainly based on rational expectations theory and efficient market hypothesis.
Keywords: LOSS AVERSION; PROSPECT-THEORY; JUDGMENT; MARKETS; LONG